Rice husk ash-based selective absorbent with imprinted ionic for gold recovery - Hastuti, Sri; Fajariani, Ema N.; Candraningrum, Intan K.; Martini, Tri; Wahyuningsih, Sayekti; Aini, Fitri N. (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2024)
The recovery of gold from aqueous solutions is crucial due to its economic value and environmental significance, making effective separation technologies essential. To tackle this challenge, development of an adsorbent with enhanced selectivity and high adsorption capacity against Au(III) is highly crucial. This present study harnessed rice husk derived-silica functionalized by (3-trimethoxysilyl)propyldiethylenetriamine (TMPDT) using imprinted ionic method to form SiO2-TMPDT-Au-Imp, specifically designed for the selective adsorption of Au(III). SiO2-TMPDT-Au-Imp demonstrated a significantly higher adsorption capacity about 387% improvement compared to SiO2-TMPDT, highlighting its superior performance. Furthermore, in addition to exhibit several advantageous characteristics that surpass those of other materials tested, underscoring its effectiveness in Au(III) adsorption. SiO2-TMPDT-Au-Imp displayed notable selectivity in competitive metal ion solutions with the preference order of Au(III)/Fe(III) < Au(III)/Cu(II) < Au(III)/Zn(II). The developed SiO2-TMPDT-Au-Imp, in brief, represents a promising advancement in the field of material science and environmental remediation in which it offers a tailored solution for efficient and selective adsorption of Au(III). This study can also be applied for the recovery of Au(III) ions from electronic waste.